Pengaruh Pendidikan Agama Kristen Dalam Keluarga Terhadap Pertumbuhan Kerohanian Anak Berdasarkan Ulangan - Nehe, Restuman; Antak, Maria Martha (Jurnal Kala Nea, 2024)
Globalization and the passage of time have made it necessary for everyone to be proficient in science and technology and have up-to-date capabilities. However, as human life develops, it also becomes increasingly chaotic, especially in the family (the bond between parents and children), where people show little respect for parents or others, and have little interest in religion or things related to God. Therefore, it is very important to provide Christian religious education regardless of time and place, whether at home, school, or places of worship. If taken seriously, Christian religious education has a significant influence on children's spiritual development at home. This study uses a qualitative research methodology, collecting data through a literature survey. This research focuses on how Christian Religious Education is implemented at home to influence children's spiritual development and help them become more Christ-like. The family is a very suitable place to shape a child's character and nurture their spiritual development.